2020
DOI: 10.1108/sr-12-2019-0310
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced sensitivity of fiber SPR sensor by metal nanoparticle

Abstract: Purpose This paper aims to clarify the relationship between the performance of the metal nanoparticles and the sensitivity of the fiber surface plasma resonance (SPR) sensor. It proposes modeling the sensing effects of a single-mode fiber SPR sensor with a cone angle structure decorated with metal nanoparticles. This study uses the metal nanoparticles to the realize enhanced sensitivity of refractive index sensing. Design/methodology/approach This paper opted for an exploratory study using a simulation appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…As shown in Figure a, the Pd–Bi 2 WO 6 nanocomposites exhibit enhanced absorption in the visible-light region compared to the pristine Bi 2 WO 6 , and the absorbance of the catalysts in the visible-light region becomes higher and higher with increase in the Pd content, attributing to electron transportation from Bi 2 WO 6 to the Pd and the absorption of Pd nanoparticles via localized SPR. Similar results were also reported for Pd/Bi-OX photocatalysts. Furthermore, the band gap energy of Bi 2 WO 6 , as shown in Figure b, is estimated to be 2.75 eV using the formula α h ν = A ( h ν − E g ) η/2 , in which α is the absorption coefficient near the absorption edge, h is the Planck constant, A is a constant, and E g is the band gap energy. The band gap energy of Pd (1%)-Bi 2 WO 6 is decreased to be about 2.58 eV.…”
Section: Resultssupporting
confidence: 79%
“…As shown in Figure a, the Pd–Bi 2 WO 6 nanocomposites exhibit enhanced absorption in the visible-light region compared to the pristine Bi 2 WO 6 , and the absorbance of the catalysts in the visible-light region becomes higher and higher with increase in the Pd content, attributing to electron transportation from Bi 2 WO 6 to the Pd and the absorption of Pd nanoparticles via localized SPR. Similar results were also reported for Pd/Bi-OX photocatalysts. Furthermore, the band gap energy of Bi 2 WO 6 , as shown in Figure b, is estimated to be 2.75 eV using the formula α h ν = A ( h ν − E g ) η/2 , in which α is the absorption coefficient near the absorption edge, h is the Planck constant, A is a constant, and E g is the band gap energy. The band gap energy of Pd (1%)-Bi 2 WO 6 is decreased to be about 2.58 eV.…”
Section: Resultssupporting
confidence: 79%
“…Some simulation results show that the sensitivity of spherical Au NPs modification is much higher than that of gold nano-cubes and nano-triangles. This may be due to the difference in optical fiber structures and excitation angle of incident light [ 55 ]. The influence of metal NPs morphology on the performance of the optical fiber SPR sensor needs special attention and in-depth analysis in future research.…”
Section: Fiber-lspr Refractive Index Sensorsmentioning
confidence: 99%
“…Metallic nanoparticles (NPs) are an important kind of functional material as they frequently exhibit extraordinary properties and can be used in diverse applications such as catalysts, sensors, and functional substrates. In the past decades, great efforts have been made to design NPs with desired properties . However, a realistic result is found that the property and performance of NPs can be crucially influenced by their hypersensitive surface conditions, exhibiting surface-dominant behaviors. For example, tin (Sn), silver (Ag), and copper (Cu) NPs with energetic surfaces are found to deform in a liquid-/rubber-like fashion at room temperature, showing discrepant mechanical behaviors in contrast to the plastic fashion observed in their bulk counterparts. Metallic NPs with the same crystalline structures but different surface chemistry conditions show inconsistent thermal-related properties including melting behavior, sublimation scenario, coalescence and sintering, and so forth.…”
Section: Introductionmentioning
confidence: 99%